2005
DOI: 10.1038/nature04219
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of HP1–chromatin binding by histone H3 methylation and phosphorylation

Abstract: Tri-methylation of histone H3 lysine 9 is important for recruiting heterochromatin protein 1 (HP1) to discrete regions of the genome, thereby regulating gene expression, chromatin packaging and heterochromatin formation. Here we show that HP1alpha, -beta, and -gamma are released from chromatin during the M phase of the cell cycle, even though tri-methylation levels of histone H3 lysine 9 remain unchanged. However, the additional, transient modification of histone H3 by phosphorylation of serine 10 next to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
786
3
14

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 872 publications
(869 citation statements)
references
References 47 publications
55
786
3
14
Order By: Relevance
“…In the case of Aurora B, Sgo appears not to be the only relevant target of the kinase in this prophase pathway. Other possible targets could be condensin, heterochromatin protein 1 (HP1), or some other protein yet to be identified (Fischle et al 2005;Hirota et al 2005;Lipp et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…In the case of Aurora B, Sgo appears not to be the only relevant target of the kinase in this prophase pathway. Other possible targets could be condensin, heterochromatin protein 1 (HP1), or some other protein yet to be identified (Fischle et al 2005;Hirota et al 2005;Lipp et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing that the amino acids in the histone H3 tail recognized by WDR5, in particular R2 and T3, are known to be methylated and phosphorylated in vivo. Couture et al (16) showed that these PTMs inhibit WDR5 binding, and this lends further credence to the concept of a "phosphomethyl switch" in which the modification status of the histone tail regulates its ability to undergo subsequent PTMs (20).…”
Section: Subsequent Inmentioning
confidence: 87%
“…Further, combinations of multiple modifications result in a context-dependent outcome on transcription (reviewed in . For example, H3K9me3 generally recruits HP1 to repress transcription, but in combination with phosphorylation of the adjacent H3S10, HP1 binding is abrogated and repression may be relieved (Fischle et al, 2005;Mateescu et al, 2008). Thus histone and DNA modifications superimpose a rich layer of information on the underlying DNA sequence.…”
Section: Molecular Mechanism Of Transcriptional Regulation and Epigenmentioning
confidence: 99%